(untitled) (Indian Journal of Arid Horticulture, 2025)
A trial was conducted to study the influence of wheat straw mulch and different plant growth regulators on fruit set, yield and quality of custard apple. Maximum flowering duration and fruit retention was observed with wheat straw mulch + GA, (5 t/ha +50 ppm) treatments. Highest number of fruits, fruit yield, fruit diameter and fruit pulp were also recorded under same treatments. Wheat straw mulch gave 21% higher fruit yield of custard apple. However application of 20 ppm NAA was at par with GA, (50 ppm). On economic basis, 50 ppm GA, + wheat straw mulch followed by 20 ppm NAA + wheat straw mulch gave highest net income.